2007
DOI: 10.1155/2007/15803
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Antioxidant Potential and Protection of Pancreatic β‐Cells by Embelia ribes in Experimental Diabetes

Abstract: This study was designed to examine the antioxidant defense by ethanolic extract of Embelia ribes on streptozotocin-(40 mg/kg, intravenously, single-injection) induced diabetes in Wistar rats. Forty days of oral feeding the extract (100 mg/kg and 200 mg/kg) to diabetic rats resulted in significant (P < .01) decrease in blood glucose, blood glycosylated haemoglobin, serum lactate dehydrogenase, creatine kinase, and increase in blood glutathione levels as compared to pathogenic diabetic rats. Further, the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…In addition, earlier studies in our laboratory showed that ethanolic extract of E. ribes produced antihyperlipidemic and antioxidant effect in streptozotocin (STZ)-induced type-1 diabetic rats (Bhandari et al 2002). Moreover, the effect of an ethanolic extract of E. ribes on tissue antioxidants, blood pressure and glycosylated hemoglobin was investigated in streptozotocin-induced oxidative damage in rats (Bhandari et al 2007(Bhandari et al , 2008. Recently, we reported an anti-obesity effect of E. ribes ethanolic extract in a rat model of high fat diet-induced obesity (Bhandari et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, earlier studies in our laboratory showed that ethanolic extract of E. ribes produced antihyperlipidemic and antioxidant effect in streptozotocin (STZ)-induced type-1 diabetic rats (Bhandari et al 2002). Moreover, the effect of an ethanolic extract of E. ribes on tissue antioxidants, blood pressure and glycosylated hemoglobin was investigated in streptozotocin-induced oxidative damage in rats (Bhandari et al 2007(Bhandari et al , 2008. Recently, we reported an anti-obesity effect of E. ribes ethanolic extract in a rat model of high fat diet-induced obesity (Bhandari et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Bhandari et al, 82,83 have reported the antidiabetic, dyslipidemic and antioxidant activity of Embelia ribes Burm in streptozotocin-induced diabetic rats, using gliclazide as a positive control drug.…”
Section: Vidanga (Embelia Ribes)mentioning
confidence: 99%
“…The main active medicinal component in dried fruits of E. ribes is embelin (2, 5-dihydroxy-3-undecyl-2,5-cyclohexadiene-1,4-benzoquinone). This highly valuable medicinal plant has been shown to have antihelmintic [3], antifertility [4,5], antibacterial [6], antidiabetic [7], antitumor, analgesic, antiinflammatory [8,9], antispermatogenic [10], chemopreventive [11] and cardioprotective [12] properties, besides antioxidant activity against methionine-induced hyperhomocysteinemia and hyperlipidemia and oxidative stress in the brain [13].…”
Section: Introductionmentioning
confidence: 99%